PENERAPAN LOCATION BASE SERVICE UNTUK MEMPERKENALKAN HOTEL DAN WISATA KULINER DI KOTA PEKALONGAN BERBASIS AUGMENTED REALITY - Wachid Darmawan; Ichwan Kurniawan; Akhmad Fuady Rifqiyanto (JURNAL LITBANG KOTA PEKALONGAN, 2019)
Pekalongan City is one of the batik producers in the national even international level. Besides batik tourism, Pekalongan City also has many interesting places that need to be explored. Therefore many hotels and culinary tours have sprung up. The obstacle faced by tourists is the number of hotels and culinary locations which are quite difficult to detect because they are not on the Pantura line. Responding to these problems, it is necessary to make an application that can handle these problems, one of them is the application of location based service to introduce hotels and culinary t ours in the city of Pekalongan based on augmented reality. In making the application using the waterfall method used for software development. As for the collection of data using observation and interview methods. This application can find out the destination location and the information available at its destination. By using the application you can find out the destination location in more detail, because in the application can know the position of the location to be located on the right or the left, so it's easier to find the location. To develop the application to the next stage the developer can add location and user usage engine usage. In addition to the layar to find out the level of accuracy between existing engines. Keywords: Local base service, Hotels, Culinary tours, Augmented reality, Layar